Assistance in Learning the History of the Arabic Language during the Umayyad Era for Teachers and the Community - Kamaluddin Abu Nawas; Muhammad Asmariadi Arsyad; Andi Abdul Hamzah (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This Community Partnership Program (PKM) aims to enhance public historical literacy and understanding of the development of the Arabic language during the Umayyad Dynasty and its relevance to contemporary Arabic language learning. The program was implemented through a participatory educational approach consisting of lectures, interactive discussions, and participant mentoring to explore the contributions of the Umayyad Dynasty to the development of Arabic as the language of administration, government, scholarship, and Islamic civilization. The educational materials covered the Arabization policy, the development of Arabic rhetoric and literature, the transformation of Arabic poetry, and the utilization of the Islamic linguistic heritage as a valuable resource for Arabic language learning. The results of the program indicate an improvement in participants' understanding of the historical development of the Arabic language, a stronger appreciation of classical Arabic literary heritage, and greater awareness of the importance of integrating historical and cultural perspectives into Arabic language instruction. The program also encouraged participants to utilize these historical values as inspiration for developing more contextual, communicative, and culturally responsive Arabic language learning while preserving the intellectual heritage of Islamic civilization. Therefore, this Community Partnership Program contributes to strengthening historical literacy on Islamic civilization and improving the quality of Arabic language learning within the community.